Systematic Review of Traumatic Brain Injuries in Baseball and Softball: A Framework for Prevention - Cusimano, Michael D.; Zhu, Alice (Frontiers in Neurology, 2017)
Background: Traumatic brain injuries (TBIs) are an important public health challenge. The classification of baseball and softball as low contact sports and their association with extremity injuries cause individuals to overlook the risk of TBI in baseball and softball. Purpose: To summarize our knowledge of the epidemiology and risk factors of TBIs associated with baseball and softball with an aim to better design and implement preventive strategies. Methods: A search algorithm containing keywords that were synonymous to the terms “TBI”, “baseball” was applied to the following nine databases: MEDLINE, Scopus, PubMed, EMBASE, CINAHL, Healthstar, PsychINFO, AMED, Cochrane library. Cited reference lists of identified articles were also consulted yielding a total of eighty-eight articles for full review. The search was concluded on November 14, 2016. The level of evidence was evaluated according to the guidelines from Strengthening the Reporting of Observational Studies in Epidemiology statement. Results: Twenty-nine articles published between 2000-2016 met the criteria for analysis. Collectively, they examined the years 1982-2015 and identified 242,731 baseball-and softball-related TBIs. The most explored outcome of TBI was concussion. The average injury rate per 1000 athletic exposures was 0.13 (range 0.03-0.46). The most common mechanism of injury was being struck by bat for younger players and being struck by ball for older athletes (adolescent and beyond). Rates of TBI were on average 4.17 times greater in games compared to practices. Females were on average 2.04 times more likely to sustain a TBI than males. Severity of TBIs varied considerably from mild and returning to the field on the same day, to immediate death. Generally, there is poor compliance with helmet use and return-to-play post-concussion guidelines. An increase TBI rates was observed over time. Multifaceted preventive strategies must be implemented to reduce the frequency and burden of these injuries. Conclusion: It is difficult to compare the epidemiologic trends of TBI in baseball and softball due critical differences in the methods employed across the studies. Additional research is needed to provide a greater understanding of baseball- and softball- related TBI, and to aid in the development of prevention and management modules.